2009
DOI: 10.1074/jbc.m807737200
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Interactions and Composition of the Fructose 6-Phosphate Catalytic Site and the Fructose 2,6-Bisphosphate Allosteric Site of Mammalian Phosphofructokinase

Abstract: Mammalian phosphofructokinase originated by duplication, fusion, and divergence of a primitive prokaryotic gene, with the duplicated fructose 6-phosphate catalytic site in the C-terminal half becoming an allosteric site for the activator fructose 2,6-bisphosphate. It has been suggested that both sites are shared across the interface between subunits aligned in an antiparallel orientation, the N-terminal half of one subunit facing the C-terminal half of the other. The composition of these binding sites and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
6
19
0
Order By: Relevance
“…In some enzymes the monomeric subunits must dimerize in order to assemble a catalytic center composed of amino acids originating from different polypeptide chains (Qian et al, 2009). In other dimeric enzymes, all the catalytically important amino acids are derived from a single polypeptide chain (Ferreras et al, 2009), and oligomerization only serves to stabilize the structure. Dimerization can also be used to increase the number of binding partners and regulate substrate affinity or selectivity (Marianayagam et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In some enzymes the monomeric subunits must dimerize in order to assemble a catalytic center composed of amino acids originating from different polypeptide chains (Qian et al, 2009). In other dimeric enzymes, all the catalytically important amino acids are derived from a single polypeptide chain (Ferreras et al, 2009), and oligomerization only serves to stabilize the structure. Dimerization can also be used to increase the number of binding partners and regulate substrate affinity or selectivity (Marianayagam et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To stimulate PFK1 activity, Fru 2,6-BP binds to a highly conserved site which, in mammals, contains Arg 566, Arg 655 and His 661. These amino acids play a key role in the binding of Fru 2,6-BP to PFK1 (Ferreras et al , 2009). Fru 2,6-BP is produced by the group of enzymes termed 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatases (PFKFB), which are encoded by the genes PFKFB1-4 .…”
Section: Phosphofructokinase 1 (Pfk1) Allosteric Regulationmentioning
confidence: 99%
“…A recent study found that UDP-GlcNAc is used to glycosylate Ser 529 on PFK1, resulting in reduced PFK1 activity in a variety of human cancer cells (Yi et al , 2012). Ser 529 is a key residue at the site where Fructose 2,6-BP binds PFK1, forming a hydrogen bond with the 2-phosphate group on Fructose 2,6-BP (Ferreras et al , 2009; Yi et al , 2012). Glucose deprivation induces OGT dependent PFK1 Ser 529 glycosylation, slowing glycolytic flux to allow glucose to be channeled elsewhere in low glucose conditions.…”
Section: Phosphofructokinase 1 (Pfk1) Allosteric Regulationmentioning
confidence: 99%
“…From recent studies, we know that the smallest active enzyme form of mammalian Pfk consists of four subunits but that higher oligomeric complexes exist that are also functional (23,24). Physiologically, AMP and M concentration of ADP promote enzyme activation, and mM concentrations of ADP and ATP promote enzyme inhibition.…”
Section: Discussionmentioning
confidence: 99%